Estudo de métodos quantitativos da geodiversidade e sua aplicabilidade na Chapada Diamantina – BA - Pires, Roger Torlay (2018)
The concept of geodiversity was proposed in the 1990s and has been gaining more and more supporters, especially among geoscientists. Despite this, the recognition by society and a larger scientific public is still at an early stage, probably due to the absence of an established conceptual and methodological framework. This includes a formal characterization of terminology and a systematization of techniques and tools to promote knowledge of geodiversity. Despite the generalized use of the concept of geodiversity in the literature, there was little progress in mapping and evaluation. Thus, there are still many gaps in the problems of methodological and even terminological transposition from ecology. To contribute to these discussions, the aim of this research was to evaluate and compare geodiversity quantification models, with Chapada Diamantina – Bahia, Brazil, as the pilot area. The quantitative methods chosen for assessing geodiversity were those of Serrano & Ruiz -Flaño, and Pereira and others. Then, after applying the procedures based on those methods with the aid of the geographic information systems, maps with geodiversity indices were generated in the territories of Morro do Chapéu and Chapada Diamantina National Park. These products were both analyzed using statistical methods and evaluated in the fieldwork. In addition, a spatial analysis methodology was proposed using the arithmetic mean of regular hexagonal and square grids, and spatial analysis to evaluate geodiversity. Some methodological limitations were found on the Serrano & Ruiz - Flaño method, such as the use of the natural logarithm in the index equation, the use of the roughness coefficient and the difficulty of comparing different areas. On the Pereira and others Method, it was verified that the choice of grid size interferes substantially with the final result of geodiversity evaluation, as well as with the choice of abiotic elements. It was concluded that the proposal to use arithmetic mean between grids decreases the subjectivity in the choice of size. Spatial analysis based on Local Moran and Getis - Ord (Gi) allowed grouping of the indices in hotspots and coldspots of geodiversity, resulting in a product that facilitates the perception of the richness of the abiotic elements of the landscape